Kepemilikan manajerial, kepemilikan institusional, dan kebijakan dividen terhadap ukuran perusahaan: Peran mediasi struktur modal - Pradani, Yolanda Sryta; Rofiuddin, Mohammad (Journal of Accounting and Digital Finance, 2024)
This study aims to determine the effect of managerial ownership, institutional ownership, and dividend policy on company size with capital structure mediation for 2016-2020. The data collection method is collecting annual financial reports on the IDX website. A sample of 26 companies was obtained with a purposive sampling technique. The analysis technique used is path analysis. The study results reveal that managerial and institutional ownership has been shown to increase company size and dividend policy, which plays a positive role in this case. Capital structure also contributes to increasing company size. However, managerial ownership, institutional ownership, and dividend policy, mediated by capital structure, do not significantly affect increasing company size.